1995
DOI: 10.1021/j100036a002
|View full text |Cite
|
Sign up to set email alerts
|

Photoassisted Chemisorption of NO on ZnO

Abstract: The effect of photoirradiation on adsorption of NO on ZnO powder was examined at 303 K, and the photoconductivity change of ZnO during adsorption of NO was also determined. Photoirradiation gave rise to a marked chemisorption of NO on ZnO. The photochemisorption led to an initial decrease and the following increase in the photoconductivity. In situ FT-IR examination showed the formation of oxidized species of NO upon photochemisorption. These results indicate two processes of the trapping of a photogenerated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The illumination of ZnO in the NO atmosphere reduces the electrical conductivity as a result of capture of a d-electron by chemisorbed NO. The capture of a quasi-free electron by a NO molecule is typical for n-type oxides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The illumination of ZnO in the NO atmosphere reduces the electrical conductivity as a result of capture of a d-electron by chemisorbed NO. The capture of a quasi-free electron by a NO molecule is typical for n-type oxides.…”
Section: Resultsmentioning
confidence: 99%
“…A small difference in the areas of lowtemperature (345−360 K) CO adsorption peaks in the dark and in the light is explained by the fact that a significant part of weakly bound CO is desorbed during evacuation before recording the TD spectrum. The illumination of ZnO in the NO atmosphere reduces the electrical conductivity 36 as a result of capture of a d-electron by chemisorbed NO. The capture of a quasi-free electron by a NO molecule is typical for n-type oxides.…”
Section: Experimental Technique and Methodsmentioning
confidence: 99%
“…However, Breedon et al have observed a rather weak, although stable, interaction of NO with the (2110) crystal face of ZnO . In other experiments, a photoinduced adsorption of NO on ZnO has been shown, that is, NO physisorbs under dark conditions but attaches strongly when ZnO is photoirradiated . Another example of chemisorbed NO x on a metal oxide surface, and hence unsuitable to form a CT complex, has been recently provided by Kang, who employed the DFT to predict the strong adsorption of NO 2 on MgO (100).…”
Section: Resultsmentioning
confidence: 99%
“…The chemisorbed species on the solid surface has been widely studied and almost established methods are available for determination of the different chemisorbed species. For example, representative five species of chemisorbed O 2 , O 2 - , O 2 2- , O - , and O 2- are evident with the aid of IR and ESR for O 2 chemisorbed on the surface of transition metal oxides. , However, interactions in physical adsorption, even micropore filling, are so weak that we have no established method for assignment of the different physisorbed states. The interaction potential profiles of an O 2 molecule with the slit graphite was obtained using Steele's 10−4−3 potential funciton and the Lennard-Jones parameters, as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%